Extension education program of Camarines Sur Agricultural College, Pili, Camarines Sur - Demandante, Brenda Rabina
The study aims to evaluate the contributions of the extension education programs organized by the Camarines Sur Agricultural College for the purpose of educating farmers through training programs in crop and animal production. The researcher conducted interviews and analyzed documents and school records which have pertinent bearing on the study. Respondents numbered 50 farmers who have undergone the training and 50 who have not. From the foregoing findings, it can be inferred that farmer-recipients were willing to change and incorporate new methods in their farm activities, that the program has been implemented successfully despite its very limited budget, and that it has served to facilitate change by inculcating a number of desirable farming values.